الحماية المدنية لبرامج الحاسب الآلي في القوانين اليمنية دراسة وصفية تحليلية - محمد علي محمد قيس (Hebron University Research Journal (Humanities), 2018)
Intellectual property began to take shape and come into existence as a legal concept with the scientific renaissance in Yemen. The state enacted laws to protect the creators and owners of innovation, inventions in all fields, where the Yemeni state became aware of the fact that its development and prosperity is based on the production of its thinkers. Thus, there is a need to protect their rights and the the electronic software user. Through a descriptive analytical approach, this paper discusses a contemporary issue which is the issue of the protection of computer programs in the Yemeni laws.